2016
DOI: 10.1155/2016/5463514
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Axillary Artery Occlusion after Reverse Total Shoulder Arthroplasty

Abstract: Axillary artery injury has been associated with shoulder dislocation and surgery. We describe a case of delayed axillary artery occlusion after reverse total shoulder arthroplasty. The injury was confirmed by Doppler and angiography and was treated with angioplasty and stenting. Early recognition and treatment of this injury are mandatory for patients' recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…Two reports have been published about AA injury after RSA for PHF. 5 , 12 Omar et al reported a case complicated by AA obstruction 2 months after RSA for PHF, and Wingert et al experienced a case treated with blood vascular reconstruction surgery for AA avulsion during RSA. Upper rim length extension was one of the features caused by RSA, 11 and this change might have damaged the AA in elderly patients with weak blood vessel walls.…”
Section: Discussionmentioning
confidence: 99%
“…Two reports have been published about AA injury after RSA for PHF. 5 , 12 Omar et al reported a case complicated by AA obstruction 2 months after RSA for PHF, and Wingert et al experienced a case treated with blood vascular reconstruction surgery for AA avulsion during RSA. Upper rim length extension was one of the features caused by RSA, 11 and this change might have damaged the AA in elderly patients with weak blood vessel walls.…”
Section: Discussionmentioning
confidence: 99%
“…Obstruction of the axillary artery in baseball pitchers results primarily from damage to the intima caused by repetitive compression of the pectoralis minor muscle by the tendon, the head of the humerus, or both during pitching [6]. There are some reported cases of arterial injury after shoulder surgery or central venous catheter insertions or radiation therapies causing AAO [7, 8]. In these reports, patients experienced hand numbness, cold sensations, and decreased strength, and radial pulses were not palpable.…”
Section: Discussionmentioning
confidence: 99%
“…Iatrogenic catheter-induced arterial injury may cause ischemic upper extremity disease, but such cases are rare. There are two reports on complications during transcatheter aortic valve replacement (1) and shoulder arthroplasty (2) , both of which were treated surgically. Transluminal angioplasty is another treatment option and shows excellent upper limb salvage for traumatic cases (3) , but reports on endovascular treatment (EVT) for iatrogenic cases are rare.…”
Section: Introductionmentioning
confidence: 99%